Entrepreneurship Training for Senior High School Visual Arts Graduates (Case Studies Kumasi and Accra Metropolis) - Kokotah, Gabriel (2011)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the degree of Master of Art in Art Education